Wage and Productivity Dispersion in United States Manufacturing: The Role of Computer Investment - Dunne, Timothy; Foster, Lucia; Haltiwanger, John; Troske, Kenneth R. (Journal of Labor Economics, 2004)
Using establishment‐level data, we shed light on the sources of the changes in the structure of production, wages, and employment that have occurred over recent decades. Our findings are: (1) the between‐plant component of wage dispersion is an important and growing part of total wage dispersion; (2) much of the between‐plant increase in wage dispersion is within industries; (3) the between‐plant measures of wage and productivity dispersion have increased substantially over recent decades; and (4) a significant fraction of the rising dispersion in wages and productivity is accounted for by changes in the distribution of computer investment across plants.